Peripheral Giant Cell Granuloma in a Child Associated with Ectopic Eruption and Traumatic Habit with Control of Four Years - Luiz Evaristo Ricci Volpato; Cristhiane Almeida Leite; Brunna Haddad Anhesini; Jéssica Marques Gomes da Silva Aguilera; Álvaro Henrique Borges (Hindawi Limited, 2016)
Peripheral giant cell granuloma (PGCG) is a nonneoplastic lesion that may affect any region of the gingiva or alveolar mucosa of edentulous and toothed areas, preferentially in the mandible and rarely occurring in children. This report describes the clinical and histopathological findings of a PGCG diagnosed in the maxilla of a 9-year-old boy associated with a tooth erupting improperly and a traumatic habit. The patient did not present anything noteworthy on extraoral physical examination or medical history, but the habit of picking his teeth and "poking" the gingiva. The oral lesion consisted of an asymptomatic, rounded, pink colored, smooth surface, soft tissue injury with fibrous consistency and approximated size of 1.5 cm located in the attached gingiva between the upper left permanent lateral incisor and the primary canine of the same side. Excisional biopsy was performed through curettage and removal of the periosteum, periodontal ligament, and curettage of the involved teeth with vestibular access. The histopathological analysis led to the diagnosis of PGCG. The prompt diagnosis and treatment of the PGCG resulted in a more conservative surgery and a reduced risk for tooth and bone loss and recurrence of the lesion. After four years of control, patient had no relapse of the lesion and good gingival and osseous health.